THE ROLE AND CLASSIFICATION OF MILITARY TERMINOLOGY IN LINGUISTICS - Gofurova Sarvara Madaminjonovna (Bright Mind Publishing, 2025)
The article discusses the role and classification of military terminology within the framework of linguistics. It highlights that military terms are not limited to the military sphere but also serve as essential communicative tools in political, legal, diplomatic and scientific discourse. From the perspective of cognitive linguistics, the semantic system of military vocabulary is explained through metaphor, conceptual models and cognitive symbols.
Keywords: Military terminology, linguistics, cognitive approach, metaphor, conceptual model, structural-semantic analysis, sociocultural factors.